Long‐term outcomes of heart transplant recipients with hepatitis C positivity: the data from the U.S. transplant registry. Issue 12 (8th November 2016) - Stepanova, Maria; Locklear, Trevor; Rafiq, Nila; Mishra, Alita; Venkatesan, Chapy; Younossi, Zobair M.
Abstract: Background: Chronic HCV infection is often considered a contraindication for receiving a heart transplantation. Methods: From the Scientific Registry of Transplant Recipients, we selected all adults with and without HCV infection who underwent a single‐organ heart transplantation in 1995‐2013; the mortality status was updated in September 2015. Results: A total of 32 812 heart transplant recipients were included; N=756 (2.30%) HCV positive. Post‐transplant patients were discharged alive at similar rates regardless of their HCV status ( P =.10). Despite this, mortality in HCV+ heart transplant recipients was consistently higher throughout post‐discharge follow‐up ( P <.002). In multivariate survival analysis, being HCV+ was independently associated with a higher post‐transplant mortality: adjusted hazard ratio 1.35 (1.16‐1.56), P <.0001. Other predictors of lower post‐transplant survival included being obese at transplant and pre‐transplant history of comorbidities (type 2 diabetes, COPD, hypertension) (all P <.05). No association of HCV infection with graft loss rates or time to graft loss was found (all P >.23). Conclusion: Chronic hepatitis C infection is associated with a significantly increased post‐transplant mortality in heart transplant recipients. The introduction of new direct‐acting antiviral agents may provide a treatment option for HCV pre‐ or post‐heart transplantation which could have a positive impact on patients' survival.